Cost-effectiveness of reducing emissions from tropical deforestation, 2016–2050. (20th December 2017) - Busch, Jonah; Engelmann, Jens
Abstract: Reducing tropical deforestation is potentially a large-scale and low-cost strategy for mitigating climate change. Yet previous efforts to project the cost-effectiveness of policies to reduce greenhouse gas emissions from future deforestation across the tropics were hampered by crude available data on historical forest loss. Here we use recently available satellite-based maps of annual forest loss between 2001–2012, along with information on topography, accessibility, protected status, potential agricultural revenue, and an observed inverted-U-shaped relationship between forest cover loss and forest cover, to project tropical deforestation from 2016–2050 under alternative policy scenarios and to construct new marginal abatement cost curves for reducing emissions from tropical deforestation. We project that without new forest conservation policies 289 million hectares of tropical forest will be cleared from 2016–2050, releasing 169 GtCO2 . A carbon price of US20/tCO2 (50/tCO2 ) across tropical countries would avoid 41 GtCO2 (77 GtCO2 ) from 2016–2050. By comparison, we estimate that Brazil's restrictive policies in the Amazon between 2004–2012 successfully decoupled potential agricultural revenue from deforestation and reduced deforestation by 47% below what would have otherwise occurred, preventing the emission of 5.2 GtCO2 . All tropical countries enacting restrictive anti-deforestation policies as effective as those in the Brazilian Amazon between 2004–2012 would avoid 58 GtCO2 from 2016–2050.